Development of Collaborative Contractual Framework for Building Information Modelling Enabled Construction Projects - Alwash, Adam (Curtin University, 2020)
The need for greater collaboration and communication are leitmotivs have been identified as core issues that need to be improved in the construction industry. A conceptual governance framework was developed to determine the relationships and interactions of the dimensions of collaboration required to improve the performance of BIM-enabled projects. Then, using precedents from case-law, the core dimensions of collaboration that are identified are legitimised and therefore, can be considered in conjunction with existing contract forms.